2021
DOI: 10.1111/jir.12871
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient adequacy, dietary patterns and diet quality among children with and without intellectual disabilities

Abstract: Background Children with intellectual disabilities (ID) frequently have feeding problems, but there has been limited research on nutrient intake, dietary patterns and diet quality in this population. Method Nutrient intakes, dietary patterns and the Healthy Eating Index were compared between 48 children with ID and 55 typically developing (TD) children aged 3–8 years who participated in the Children's Mealtime Study. Three‐day food records that included two weekdays and one weekend day were used to assess diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In the case-control study of Marí-Bauset et al, children with autism between the ages of 6-10 were found to have higher daily vitamin E intake compared to healthy children; and a positive deviation from the reference was observed in the same age group (p=0.000) (Marí-Bauset et al, 2015). Bandini et al (2021) investigated the differences between typically developing children and children with intellectual disabilities in the aspect of nutrition. According to this study results, it was stated that children had Estimated Average Requirement/Adequate Intake (EAR/AI) for most nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…In the case-control study of Marí-Bauset et al, children with autism between the ages of 6-10 were found to have higher daily vitamin E intake compared to healthy children; and a positive deviation from the reference was observed in the same age group (p=0.000) (Marí-Bauset et al, 2015). Bandini et al (2021) investigated the differences between typically developing children and children with intellectual disabilities in the aspect of nutrition. According to this study results, it was stated that children had Estimated Average Requirement/Adequate Intake (EAR/AI) for most nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…A registered dietitian and a nutrition student led 35‐min nutrition education sessions that focused on food group identification, making healthy food choices, snack preparation, and taste testing, as follows: nutrition lessons were activity‐ and game‐based, such as playing ‘Protein Bingo’ to identify protein foods; weekly taste tests entailed simple food preparation and tasting foods that corresponded with the session's lesson; the lessons were derived from previously developed nutrition education modules used in our prior interventions (Bandini et al, 2021; Curtin et al, 2013) and included in a published nutrition education curriculum we developed (Bandini et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Data from the 2015 Youth Risk Behavior Surveillance Survey suggest that a substantial number of youth do not meet dietary guidelines; for example, on a daily basis only 61% of high school youth consumed more than one vegetable and only 63% consumed more than one serving of fruit or 100% fruit juice (Centers for Disease Control and Prevention, n.d.). Although data on dietary intake of children with intellectual disabilities are limited, a growing literature suggests that many do not meet the dietary guidelines for fruit and vegetable intake and that their diets are high in added sugars (Bandini, Curtin, et al, 2021; Bandini, Eliasziw, et al, 2021; Buro et al, 2021; Ptomey et al, 2020; Subach, 2018). Barriers to healthy eating include lack of knowledge about healthy eating, easy accessibility to high calorie low nutrient dense foods, and a complex food environment that makes decision‐making around food choices difficult.…”
Section: Introductionmentioning
confidence: 99%
“…(3,8) Children with intellectual disabilities, such as autism spectrum disorder, are likely to be at risk of inadequate intake of minerals and vitamins because of their preferences for specific food textures, colors, and flavors. (9,10) Adequate nutritional support may restore linear growth, decrease irritability, reduce the frequency of hospitalization, and increase social participation. (3,11,12) Many studies have reported inadequate intake of micronutrients, such as calcium, iron, and zinc in children with disabilities in Western and Middle Eastern countries.…”
Section: Introductionmentioning
confidence: 99%